More Than Just a Simple Farm Game: LGBTIQ+ representations and possibilities in cozy country life simulators - Ojeda-García, Francisco Miguel (Estudios LGBTIQ+, Comunicación y Cultura, 2026)
Farm life simulators have long been a significant niche within the video game industry. Whit more than twenty years of history, these titles – commonly know as farming games – have evolved to respond not only to gameplay and aesthetic trends, but also to new social and cultural demands. In this context, it is particularly noteworthy how developers have begun to explicitly incorporate representations and experiences of LGBTIQ+ communities. Although it may seem counterintuitive to associate LGBTIQ+ diversity with rural settings, cozy farming games are increasingly committed to broadening gender expression and relationship options, allowing players to choose partners freely, free from prejudice or limitations. This article aims to examine in detail the LGBTIQ+ possibilities offered by one of the most recent farming simulators, Story of Seasons: Grand Bazaar (Xseed Games, 2005). To this purpose, the results, which emerge from a formal analysis of the content and an autoethnographic ingame study, are structured around three key dimensions: 1) avatar customization options and forms of identity expression; 2) narrative development and the discursive construction of the game; 3) mechanics for establishing romantic relationships and forming LGBTIQ+ families.
Keywords: Cozy Games; LGBTIQ; Videogames; Farming Simulators; Identification; Gender Identity